Performance analysis of indirect diesel injection combustion (IDI) for heavy duty V16 diesel engine by numerical simulation - Elrakb, Ahmed (My University, 2019)
CI dizel motorların yüzyıllık geçmişi olmasına rağmen, araştırmacılar motor geliştirmeyi bugüne kadar halen sürdürmektedir. Araştırmacılar, azalan fosil yakıt kaynakları ve katı emisyon kuralları sebebiyle geliştirmelerini hızlandırmaktadırlar. Bu sebeple, üç ana stratejik görevler ; Optimum yakıt tüketimi, Düşük gaz emisyonları, ve Yüksek motor performansı hedef alınmaktadır.Yukarıdaki hedefleri deneysel ve hesaplamalı yöntemlerle ulaşılabilir. İçten yanmalı motorun bilgisayarlı modelleme işlemleri, deneysel çalışmalara nazaran, genişletilmiş parametrik çalışmalarda daha kullanışlıdır.Bu çalışmada endirekt injeksiyon (IDI) sistemine sahip 16 silindir V tipi 16PA4-185 motorun performansı çalışılacaktır. Belirli bir geometride, enjeksiyon karakteristiklerinde ve yakıt özelliklerinde, motor modeli oluşturulacak ve bütün tipik motor performans parametreleri elde edilecektir.Motorun oluşturulmasındaki değişkenler üretici tarafından verilecektir. Ancak bazı parametreler, tez danışmaının isteği üzerine varsayımsal olarak alınacaktır. Motorun numerik simülasyon modeli, iş istasyonuna uyumlu bir ağ çözümü ile oluşturulacak, dolayısıyla işlemsel maliyete karşın model çıktısının doğruluğu optimize edilecektir.Birçok durum çalışması, bazı motor parametrelerini değiştirerek, sonuca ve karşılaştırmaya varmak amaçlı dikkate. alınacaktır ve ön yanma odasına ve diğer enjeksiyon profil verilerine bağlı önermeler oluşturulacaktır.

Although compression ignition (CI) diesel engines were discovered a century ago, researchers continue to contribute in engine development till date as they are motivated by the continuous depletion of hydrocarbon fossil fuel resources and by the stringer government environmental regulations. Therefore, three strategic objectives were always targeted: optimal fuel economy, reduced gas emissions, and outstanding engine performance.Above objectives can be achieved by combination of advanced experimental and computational studies. The modelling of internal combustion engines has an absolute advantage over the experimental approach. Engine modelling is useful to carry out extensive parametric studies that allow for optimization of engine variables. In addition, modelling cost less and consume shorter time than experimentation. Nevertheless, experimentation is essential to fine-tone the design and validate the proposed model results.This paper studying the performance of CI engine that utilizes indirect diesel injection (IDI) on heavy duty locomotive 16-cylinders V-type engine model number 16 PA 4 – 185, by utilizing a commercial numerical simulation software.For a given geometry, injection characteristics, and fuel properties, the engine model will be developed and all typical engine performance parameters will be evaluated. Traditionally, the torque, power and specific fuel consumption of the engine will be obtained. These curves represent the benchmark for comparison with any other results that will be obtained after changing some of the model parameters.The engine variables that required to establish the model will be adopted from the engine specification provided by the manufacturer. However, some parameters will be approximated using available data from literature or common internal combustion engine engineering sense.The numerical simulation model will be constructed with specification (i.e. mesh resolution) suitable for the workstation to be utilized and in a manner that will optimize the computational cost versus the accuracy of the model output.
Keywords: diesel; Diesel motor; dizel; Dizel motor; endirekt; enjeksiyon; indirect; injection; Makine mühendisliği; Mechanical engineering; motor; simulation; simülasyon engine